2002
DOI: 10.1021/ac025659x
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Pressure Photoionization Mass Spectrometry. Ionization Mechanism and the Effect of Solvent on the Ionization of Naphthalenes

Abstract: The ionization mechanism in dopant-assisted atmospheric pressure photoionization and the effect of solvent on the ionization efficiency was studied using 7 naphthalenes and 13 different solvent systems. The ionization efficiency was 1-2 orders of magnitude higher with dopant than without, indicating that the photoionization of the dopant initiates the ionization process. In positive ion mode, the analytes were ionized either by charge exchange or by proton transfer. Charge exchange was favored for low proton a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
321
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(337 citation statements)
references
References 28 publications
13
321
1
2
Order By: Relevance
“…Kauppila et al [27,28] studied background ions from common LC solvents and APPI dopants for NI-APPI. However, many important background ions were not detected because the mass spectrometers discriminated against low m/z values.…”
Section: Analysis Of Lc Solvents and Appi Dopantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kauppila et al [27,28] studied background ions from common LC solvents and APPI dopants for NI-APPI. However, many important background ions were not detected because the mass spectrometers discriminated against low m/z values.…”
Section: Analysis Of Lc Solvents and Appi Dopantsmentioning
confidence: 99%
“…One such application has been further demonstrated in the detection and identification of background ions generated from common LC solvents and APPI dopants. Previous NI-APPI studies by others [27,28] have not detected and/or identified many important background ions from common LC solvents and APPI dopants, partly because the mass spectrometers discriminated against low m/z values. In addition, the resolution of those mass spectrometers was also low, making it difficult to identify the detected ions.…”
mentioning
confidence: 99%
“…The aim of this work is to study, in detail, the relevant reactions so that LC/EC-APPI-MS development can be better guided toward analysis of low polarity compounds in the future. The basic principle of APPI is the formation of a molecular radical cation caused by the absorption of a photon by a molecule, and is accompanied by the formation of a thermal electron [9]. In dopant assisted negative ion-APPI, the ionization process is initiated by thermal electrons.…”
mentioning
confidence: 99%
“…The basic principle of APPI is the formation of a molecular radical cation caused by the absorption of a photon by a molecule, and is accompanied by the formation of a thermal electron [9]. In dopant assisted negative ion-APPI, the ionization process is initiated by thermal electrons.…”
mentioning
confidence: 99%
“…APPI is a valuable complement to atmospheric pressure chemical ionization (APCI) and electrospray ionization (ESI) and is helping to extend the range of molecules that can be efficiently ionized. However, it is fair to say that the growth in usage of APPI and development of new applications is outpacing work to understand the fundamental mechanism of PI at elevated pressures [10,11,12].…”
mentioning
confidence: 99%